2017
DOI: 10.1007/s12010-017-2642-x
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Receptor-Targeted Magnetosome and HSA-Coated Iron Oxide Nanoparticles as MRI Contrast-Enhancing Agent in Animal Cancer Model

Abstract: Magnetosomes are specialized organelles arranged in intracellular chains in magnetotactic bacteria. The superparamagnetic property of these magnetite crystals provides potential applications as contrast-enhancing agents for magnetic resonance imaging. In this study, we compared two different nanoparticles that are bacterial magnetosome and HSA-coated iron oxide nanoparticles for targeting breast cancer. Both magnetosomes and HSA-coated iron oxide nanoparticles were chemically conjugated to fluorescent-labeled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 49 publications
1
23
0
Order By: Relevance
“…[ 315 ] Magnetic nanoparticles increase proton magnetic resonance absorption and consequently enhance the sensitivity and specificity of MRI. [ 316 ] Magnetosomes, which are magnetic nanoparticles of biological origin, provide better contrast for MRI than current magnetic iron oxide nanoparticle formulations possibly because of their larger size and high monodispersity. [ 317 ]…”
Section: Applicationsmentioning
confidence: 99%
“…[ 315 ] Magnetic nanoparticles increase proton magnetic resonance absorption and consequently enhance the sensitivity and specificity of MRI. [ 316 ] Magnetosomes, which are magnetic nanoparticles of biological origin, provide better contrast for MRI than current magnetic iron oxide nanoparticle formulations possibly because of their larger size and high monodispersity. [ 317 ]…”
Section: Applicationsmentioning
confidence: 99%
“…The distinctive characteristics of BMs suggested that they could be used as an effective vehicle, particularly as a potential magnetic carrier for drugs. BMs have been used as vehicles for antibodies, nucleic acids, and proteins in the laboratory . In our study, we developed a convenient way to conjugate antibodies to BMs.…”
Section: Discussionmentioning
confidence: 99%
“…The co‐precipitation method was utilised to synthesise SPIONs [14]. Briefly, 60 ml 0.5% HCl solution was placed in a flask and nitrogen gas was purged through the solution for 15 min to remove any oxygen.…”
Section: Methodsmentioning
confidence: 99%